A kind of vinylene carbonate modified olefin-norbornene copolymer microsphere and preparation method thereof
By adopting a core layer cladding structure of vinylene carbonate modified olefin-norbornene copolymer and polysulfone resin, combined with hot drawing preparation and fluid instability within the fiber, the technology of existing polymer microsphere preparation methods is solved. Difficulty and shortcomings to prepare microspheres with excellent physical and chemical properties, improving application quality and modifiability.
Patent Information
- Application Number
- CN202411276976.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Existing polymer microsphere preparation methods such as membrane emulsification method and microfluidic control method have technical difficulties and shortcomings, resulting in rough appearance, poor size uniformity, poor monodispersity, and olefin-norbornene copolymer microspheres in high-energy electrons. After beam irradiation, the surface wrinkles, poor density and poor spherical shape will affect the application quality.
Vinylene carbonate modified olefin-norbornene copolymer is used as the core material, combined with polysulfone resin as the cladding material. It is prepared by hot drawing of the core rod and the cladding rod, and uses the instability of the fluid in the fiber to prepare the microfiber. spheres, control the diameter ratio of cladding rods and core rods and the number of fiber iterations, and adjust the diameter and number of microspheres.
The prepared microspheres have excellent monodispersity, uniform particle size, smooth surface, and good shape, which improves the application quality and modifiability of the microspheres and can maintain surface stability under high-energy electron beam irradiation.
Smart Images

Figure CN118791673B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high molecular polymer microspheres, in particular to vinylene carbonate modified olefin-norbornene copolymer microspheres and a preparation method thereof. Background Art
[0002] Polymer microspheres are tiny spheres made of polymer materials, usually with diameters ranging from a few microns to hundreds of microns. Polymer microspheres are widely used in many fields, such as drug delivery, catalyst carriers, inks, coatings and composite materials, and because of their high specific surface area, adjustable pore structure and surface functionalization, they also have broad application prospects in environmental remediation, separation and filtration. Due to their adjustable properties, polymer microspheres are of great significance in scientific research and engineering.
[0003] At present, the common methods for preparing polymer microspheres are usually membrane emulsification and microfluidics, which can be used to prepare micron or nanometer-scale particles, but both methods have certain technical deficiencies and difficulties in preparation. In the membrane emulsification method, the average pore size of the membrane is related to the stability of the emulsion. The larger the pore size of the membrane, the better the stability of the emulsion, but the pore size determines the distance between adjacent pores. The larger the pore size, the smaller the distance between adjacent pores, resulting in the rough appearance of the prepared microspheres, poor size uniformity, and poor monodispersity; in addition, the interface control between the film and the emulsion is also a key difficulty, which will also affect the size distribution and morphology of the microspheres. In the microfluidics method, the preparation and application of microfluidic chips is a difficulty. The design and preparation of microfluidic channels require high-precision processing and surface treatment, which not only increases the preparation cost, but also increases the difficulty of the process. In addition, in the microfluidics method, it is also necessary to accurately control the fluid flow rate and pressure, as well as accurately control the synthesis process of the microspheres, which also brings certain difficulties to the preparation.
[0004] In addition, research has found that olefin-norbornene copolymer materials can be used as good bulk materials for copolymer microspheres because of their advantages such as easy processing, low production cost, easy modification of channel surfaces, and good biocompatibility. However, during the preparation process, it was found that microspheres prepared based on olefin-norbornene copolymers would have obvious wrinkles after being irradiated under a scanning electron microscope for a period of time, the smoothness of the microsphere surface was poor, and the poor density of the microspheres when preparing microspheres with larger particle sizes led to pores on the surface and poor sphericity of the microspheres, which seriously affected the modifiability of the microspheres. These problems also affected the application quality of the microspheres. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies of the above-mentioned prior art, the present invention provides a vinylene carbonate modified olefin-norbornene copolymer microsphere and a preparation method thereof. The preparation method of the present invention uses vinylene carbonate modified olefin-norbornene copolymer as a core layer material to make a core layer rod, uses polysulfone resin as a cladding material to make a cladding rod, inserts the core layer rod into the cladding rod and vacuum heat treats it to make a preform rod, and then obtains a primary fiber by hot drawing. The primary fiber can also select the number of iterations according to the preparation needs to obtain a fiber of the corresponding order, and then utilizes the unstable characteristics of the fluid in the fiber to prepare the microsphere. The microspheres prepared by the present invention have excellent physical and chemical properties such as monodispersity, uniform particle size, smooth microsphere surface, and good morphology.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A vinylene carbonate modified olefin-norbornene copolymer microsphere, wherein the vinylene carbonate modified olefin-norbornene copolymer microsphere is formed by a vinylene carbonate modified olefin-norbornene copolymer, and the structural formula of the vinylene carbonate modified olefin-norbornene copolymer is: ,
[0008] Where 0≤X i , 0≤Y i , 0≤Z i , 0≤W i , and X i , Y i , Z i Not at the same time 0, 821≤∑(X i +Z i )≤1027,240≤∑Y i ≤300,1083≤∑W i ≤1354.
[0009] As a further technical solution of the present invention, the average molecular weight of the vinylene carbonate modified olefin-norbornene copolymer is 200,000-250,000.
[0010] As a further technical solution of the present invention, the particle size of the vinylene carbonate modified olefin-norbornene copolymer microspheres ranges from 50 nm to 2 mm.
[0011] A method for preparing vinylene carbonate modified olefin-norbornene copolymer microspheres comprises the following steps:
[0012] (1) Preparation of core layer material: dissolving olefin-norbornene copolymer in toluene solution, stirring evenly at 40-50° C., adding vinylene carbonate and appropriate amounts of 2-ethylhexyloxytitanic acid and azobisisobutyronitrile, and obtaining a mixed solution containing vinylene carbonate modified olefin-norbornene copolymer after the reaction is completed, wherein the mass ratio of the added olefin-norbornene copolymer to the added vinylene carbonate is 100:(7-13.6);
[0013] (2) Preparation of core layer rod: the mixed solution obtained in step (1) is formed into a film by a coating machine, and the film is subjected to heat pressing to obtain a cylindrical core layer rod;
[0014] (3) Preparation of clad rods: hot pressing clad material masterbatch into N cylindrical clad rods, where N is a natural number greater than 0, and at least one cylindrical core cavity is symmetrically arranged with the axis of the clad rod as the symmetry axis, and the core cavity is arranged along the length direction of the clad rod;
[0015] (4) Preparation of N-grade fiber:
[0016] A plurality of core layer rods are placed in each core cavity of the first cladding rod, vacuum heat treatment is performed to obtain a first-level preform rod, and the first-level preform rod is subjected to heat drawing treatment to obtain a first-level fiber.
[0017] A plurality of primary fibers are placed in each core cavity of the second cladding rod, vacuum heat treatment is performed to obtain a secondary preform rod, and the secondary preform rod is heat-drawn to obtain a secondary fiber.
[0018] Inserting a plurality of N-1-level fibers into each core cavity of the N-th cladding rod, performing vacuum heat treatment to obtain an N-level preform rod, and performing heat drawing treatment on the N-level preform rod to obtain an N-level fiber;
[0019] (5) Heat treatment of the N-grade fiber: heat treating the N-grade fiber obtained in step (4) for 3 to 10 minutes, so that the core layer material of the N-grade fiber shrinks in the cladding material to form microspheres;
[0020] (6) Dissolution of the cladding material: The N-grade fiber obtained in step (5) is dissolved in a selective solvent for the cladding material, heated and stirred until completely dissolved, and then centrifuged at high speed for 5 minutes. Then, an appropriate amount of the selective solvent for the cladding material is added and ultrasonicated for 10 minutes. After repeated centrifugation and ultrasonication, the upper layer of liquid is removed and the precipitate is collected to obtain vinylene carbonate modified olefin-norbornene copolymer microspheres.
[0021] As a further technical solution of the present invention, the temperature of the vacuum heat treatment in step (4) is 80-100°C and the time is 30 minutes; the temperature of the hot drawing treatment in step (4) is 280-360°C.
[0022] As a further technical solution of the present invention, the temperature of the heat treatment in step (5) is 290-380°C.
[0023] As a further technical solution of the present invention, the diameter of the core layer rod is 2-4 mm, the diameter of the cladding rod is 20-30 mm, the number of core cavities of each cladding rod is set to 1-5, and the diameter of the core cavity is 2-25 mm.
[0024] As a further technical solution of the present invention, the value range of N is 1-4.
[0025] As a further technical solution of the present invention, the diameter of the N-level fiber obtained in step (4) is 0.6 to 4 mm.
[0026] As a further technical solution of the present invention, the cladding material is polysulfone resin.
[0027] As a further technical solution of the present invention, the selective solvent for the cladding material is selected from one of N,N-dimethylacetamide solution, N-methylpyrrolidone solution and N,N-dimethylformamide solution.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention uses vinylene carbonate to modify the olefin-norbornene copolymer, which effectively improves the fluidity, adhesion and chemical resistance of the olefin-norbornene copolymer. Therefore, the prepared microspheres have more regular spherical shapes. In the process of removing the cladding material, the surface of the microspheres has excellent chemical resistance, and does not chemically react with the selective solvent of the cladding material so that the cladding material can be fully dissolved. The surface of the obtained microspheres is also cleaner and smoother, and the rigidity of the microspheres is increased. Even under long-term irradiation of high-energy electron beams, the surface of the microspheres hardly changes.
[0030] The regularity of microspheres makes them more consistent in size and shape, which helps to achieve more stable performance when used in areas such as drug delivery and separation technology. A smooth surface of microspheres can reduce friction and enhance compatibility. A smooth surface of microspheres can reduce friction between microspheres, help improve fluidity and dispersibility, and are suitable for coatings and composite materials. Microspheres with smooth surfaces have better contact with other materials, which can improve the interfacial properties of composite materials and enhance overall mechanical properties. The rigidity of microspheres can enhance their stability under mechanical loads, making them suitable for applications that are subject to greater pressure, such as filling materials and stents. Microspheres with higher rigidity can better maintain their shape under high temperatures or chemical environments, and are suitable for applications that require high temperature or corrosion resistance.
[0031] 2. The microsphere preparation method of the present invention uses vinylene carbonate modified olefin-norbornene copolymer as the core material and polysulfone resin as the cladding material, and utilizes the unstable characteristics of the fluid in the fiber to prepare the microsphere, which can effectively solve the problems existing in the traditional membrane emulsification method and microfluidic method for preparing microspheres. During the preparation process, the diameter of the microsphere is adjusted by controlling the diameter ratio of the cladding rod and the core rod and the number of iterations of the fiber, so that the size of the microsphere can be controlled from 50 nm to 2 mm. By controlling the number of core cavities of the cladding rod, the number of core rods or fibers in the core cavity, and the number of iterations of the fiber, the number of microspheres prepared can be effectively controlled to achieve mass production of polymer microspheres.
[0032] 3. The preparation method of the present invention has simple process steps, easy operation, high controllability, and short experimental time. The microsphere particle size distribution gradient can be controlled within 2 μm, and the prepared microspheres have excellent monodispersity, uniform particle size, and smooth microsphere surface. The preparation method used in the present invention has strong universality and a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is an optical microscope image of the secondary fiber after heat treatment in Example 1;
[0034] Figure 2 An optical microscope image of the polymer microspheres obtained in Example 1;
[0035] Figure 3 is a scanning electron microscope image of the polymer microspheres obtained in Example 1;
[0036] Figure 4 is a cross-sectional image of the primary fiber in Example 2;
[0037] Figure 5 is an optical microscope image of the secondary fiber after heat treatment in Example 2;
[0038] Figure 6 An optical microscope image of the polymer microspheres obtained in Example 2;
[0039] Figure 7 The combined scanning electron microscope images of the polymer microspheres obtained in Examples 1-4;
[0040] Figure 8 is a scanning electron microscope image of the polymer microspheres obtained in Comparative Example 1;
[0041] Fig. 9 is a scanning electron microscope image of a single polymer microsphere obtained in Comparative Example 1;
[0042] Fig.10 is a scanning electron microscope image of the polymer microspheres obtained in Comparative Example 2;
[0043] Fig.11 Another scanning electron microscope image of the polymer microspheres obtained in Comparative Example 2;
[0044] Fig.12 is a scanning electron microscope image of the polymer microspheres obtained in Comparative Example 4;
[0045] Fig.13 This is a scanning electron microscope image of a single polymer microsphere obtained in Comparative Example 4. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0047] (1) Weigh 1 g of olefin-norbornene copolymer and pour it into a beaker containing 20 mL of toluene solution. Stir and heat continuously and evenly at 40°C for 40 min to completely dissolve the olefin-norbornene copolymer. Then weigh 0.05 mL of vinylene carbonate, 5 μL of 2-ethylhexyloxytitanic acid and 7 mg of azobisisobutyronitrile and add them to the beaker. Under the catalysis of the co-catalyst, the vinylene carbonate and the olefin-norbornene copolymer react to obtain a mixed solution containing the modified olefin-norbornene copolymer. In this embodiment, the mass ratio of vinylene carbonate to olefin-norbornene copolymer is 7:100. The average molecular weight of the obtained vinylene carbonate modified olefin-norbornene copolymer is ≈200,000. ∑(X i +Z i )≈821,∑Y i ≈240,∑W i ≈1083.
[0048] (2) The obtained mixed solution was made into a film with a thickness of 200 μm using a coating machine. The film was placed in two semi-cylindrical molds with a diameter of 2 mm and hot-pressed at 230 °C for 15 min. After the internal air was fully expelled, a dense semi-cylinder was obtained. The two semi-cylinders were molded together and further hot-pressed to obtain a core layer rod with a diameter of 2 mm.
[0049] (3) Put the polysulfone resin masterbatch into a mold with a diameter of 20 mm and a diameter of 30 mm respectively, and hot press it at 300°C at a pressure of 0.1-14 MP for 15 min. During this process, the pressure is continuously applied to ensure that the polysulfone resin masterbatch can be continuously subjected to pressure. The material is added every 15 min until a dense cylindrical polysulfone resin rod is obtained, of which the 20 mm diameter rod is the first cladding rod and the 30 mm diameter rod is the second cladding rod. Use a drilling machine to drill 5 cylindrical core cavities with a diameter of 2 mm in the center of the first cladding rod. The 5 core cavities are symmetrical about the axis of the first cladding rod. Drill a cylindrical core cavity with a diameter of 6 mm in the center of the second cladding rod. The core cavity is set along the length direction of the cladding rod.
[0050] (4) After inserting a core layer rod into each of the five core cavities of the first cladding rod, the first cladding rod was placed in a vacuum drying oven and heat-cured at 100°C for 30 min to obtain a primary preform rod. The primary preform rod was placed on a drawing tower and stretched for the first time at 360°C to be hot-drawn into a primary fiber with a core-cladding structure and a diameter of 600 μm.
[0051] After taking 70 primary fibers with consistent height and inserting them into the core cavity of the second cladding rod, the second cladding rod was placed in a vacuum drying oven and heat-cured at 100°C for 30 min to obtain a secondary preform rod, which was stretched for the second time at 360°C and hot-drawn into a secondary fiber with a diameter of 600 μm. The core number of the secondary fiber is 350 and the core diameter is 1.5 μm.
[0052] (5) The secondary fiber is fixed on a glass sheet and placed in a tube furnace for heat treatment at 380°C for 3 min. The instability of the fluid in the fiber and the glass transition temperature difference between the cladding material and the core material are used to shrink the core material in the cladding material to form polymer microspheres. Figure 1 As shown, under a high-power optical microscope, it can be clearly observed that the core material in the fiber shrinks into a ball.
[0053] (6) Place the heat-treated secondary fiber in a beaker containing 50 mL of N,N-dimethylacetamide solution, and heat it at 70°C and 600 rpm while stirring continuously to fully dissolve the polysulfone resin coating material. After the dissolution is complete, centrifuge the mixed solution at 13,000 rpm for 5 min to separate the polymer microspheres. In order to fully remove the coating material, re-add N,N-dimethylacetamide, sonicate for 10 min, and centrifuge again. Repeat this operation 7 times to fully remove the polysulfone resin coating, and finally remove the upper liquid and collect the precipitate to obtain the polymer microspheres. The N,N-dimethylacetamide solution was purchased from Sinopharm Chemical Reagent Co., Ltd. for analytical grade.
[0054] In this embodiment, after the primary fiber is obtained by setting 5 core cavities in the first cladding rod, it is stretched twice to obtain the secondary fiber. The particle size of the polymer microspheres obtained by heat treatment of the secondary fiber is about 3 μm, and the number of the obtained polymer microspheres is about 1.25×10 6 In order to facilitate observation, the microspheres were dispersed in N,N-dimethylacetamide solution. Figure 2 and Figure 3 As shown, the microspheres have good morphology and structure, smooth surface, good monodispersity, and good particle size uniformity. Example 2
[0055] (1) The operation method for preparing the core material in this embodiment is basically the same as that in Example 1, except that the content of vinylene carbonate is 0.07 mL, the content of 2-ethylhexyloxytitanic acid is 10 μL, and the content of azobisisobutyronitrile is 5 mg. The specific process is not repeated here. In this embodiment, the mass ratio of vinylene carbonate to olefin-norbornene copolymer is 9.5:100, and the average molecular weight of the obtained vinylene carbonate modified olefin-norbornene copolymer is ≈210000, ∑(X i +Z i )≈863,∑Y i ≈250,∑W i ≈1138.
[0056] (2) The obtained mixed solution was made into a film with a thickness of 200 μm using a coating machine. The film was placed in two semi-cylindrical molds with a diameter of 4 mm and hot-pressed at 230 °C for 15 min. After the internal air was fully expelled, a dense semi-cylinder was obtained. The two semi-cylinders were molded together and further hot-pressed to obtain a core layer rod with a diameter of 4 mm.
[0057] (3) Put the polysulfone resin masterbatch into two cylindrical molds with a diameter of 20 mm, and hot press them at 300°C with a pressure of 0.1-14 MP for 15 min. During this process, the pressure is continuously applied to ensure that the polysulfone resin masterbatch can be continuously subjected to pressure. The material is added every 15 min until a dense polysulfone resin rod is obtained, which is a first cladding rod and a second cladding rod with a diameter of 20 mm. Use a drilling machine to symmetrically drill a cylindrical core cavity with a diameter of 4 mm in the center of the first cladding rod and a cylindrical core cavity with a diameter of 6 mm in the center of the second cladding rod. The core cavity is set along the length direction of the cladding rod.
[0058] (4) After inserting the core layer rod into the core cavity of the first cladding rod, the first cladding rod is placed in a vacuum drying oven and heat-cured at 100°C for 30 min to obtain a primary preform rod. The primary preform rod is placed on a drawing tower and stretched for the first time at 360°C to be hot-drawn into a primary fiber with a diameter of 600 μm and a core-cladding structure, such as Figure 4 Shown is a cross-sectional image of a primary fiber.
[0059] Take 70 primary fibers with consistent height and insert them into the core cavity of the second cladding rod. The second cladding rod is placed in a vacuum drying oven and heat-cured at 100°C for 30 min to obtain a secondary preform rod. The secondary preform is stretched for the second time at 360°C and hot-drawn into a secondary fiber with a diameter of 600 μm. The secondary fiber has 70 cores and a core diameter of 3.6 μm.
[0060] (5) The secondary fibers are fixed on a glass sheet and placed in a tube furnace for heat treatment at 350°C for 5 min. The instability of the fluid in the fiber and the glass transition temperature difference between the cladding material and the core material are used to shrink the core material to form polymer microspheres. Figure 5 As shown, under a high-power optical microscope, it can be clearly observed that the core material in the fiber shrinks into microspheres with independent structure, uniform particle size and regular morphology.
[0061] (6) Place the heat-treated secondary fiber in a beaker containing 50 mL of N,N-dimethylacetamide, and heat it at 80°C and 600 rpm with continuous stirring to fully dissolve the polysulfone resin coating material. After the dissolution is complete, centrifuge the mixed solution at 10,000 rpm for 10 min to separate the polymer microspheres. In order to fully remove the coating material, re-add N,N-dimethylacetamide, sonicate for 10 min, and centrifuge again. Repeat this operation 7 times to fully remove the polysulfone resin coating. Finally, remove the upper layer of liquid and collect the precipitate to obtain the polymer microspheres.
[0062] In this embodiment, the secondary fibers are drawn twice to obtain the polymer microspheres, and the particle size of the polymer microspheres obtained by heat treatment of the secondary fibers is about 8 μm, and the number of the microspheres obtained is about 8.5×10 4 Particles. Figure 6 As shown, the polymer microspheres obtained in this example have good monodispersity and good particle size uniformity. Example 3
[0063] (1) The operation method for preparing the core material in this embodiment is basically the same as that in Example 1, except that the content of vinylene carbonate is 0.08 mL, the content of 2-ethylhexyloxytitanic acid is 12 μL, and the content of azobisisobutyronitrile is 8 mg. The specific process is not repeated here. In this embodiment, the mass ratio of vinylene carbonate to olefin-norbornene copolymer is 10.9:100, and the average molecular weight of the obtained vinylene carbonate modified olefin-norbornene copolymer is ≈225000, ∑(X i +Z i )≈924,∑Y i ≈270,∑W i ≈1219.
[0064] (2) The obtained mixed solution was made into a film with a thickness of 200 μm using a coating machine. The film was placed in two semi-cylindrical molds with a diameter of 4 mm and hot-pressed at 230 °C for 15 min. After the internal air was fully expelled, a dense semi-cylinder was obtained. The two semi-cylinders were molded together and further hot-pressed to obtain a core layer rod with a diameter of 4 mm.
[0065] (3) Put the polysulfone resin masterbatch into two cylindrical molds with a diameter of 20 mm, and hot press them at 300°C with a pressure of 0.1-14 MP for 15 min. During this process, the pressure is continuously applied to ensure that the polysulfone resin masterbatch can be continuously subjected to pressure. The material is added every 15 min until a dense polysulfone resin rod is obtained, which is a first cladding rod and a second cladding rod with a diameter of 20 mm. Use a drilling machine to symmetrically drill a cylindrical core cavity with a diameter of 4 mm in the center of the first cladding rod, and drill 5 cylindrical core cavities with a diameter of 2 mm in the center of the second cladding rod. The 5 core cavities are symmetrical about the axis of the second cladding rod, and the core cavities are arranged along the length direction of the cladding rod.
[0066] (4) Insert the core layer rod into the core cavity of the first cladding rod, place the first cladding rod in a vacuum drying oven, and heat cure it at 100°C for 30 min to obtain a primary preform rod, place the primary preform rod on a drawing tower, and perform the first stretching at 360°C to hot draw it into a primary fiber with a core-clad structure and a diameter of 2000 μm. The core diameter is 400 μm.
[0067] Take 5 primary fibers with consistent height and insert them into the 5 core cavities of the second cladding rod respectively. The second cladding rod is placed in a vacuum drying oven and heat-cured at 100°C for 30 min to obtain a secondary preform rod. The secondary preform is stretched for the second time at 360°C and hot-drawn into a secondary fiber with a diameter of 600 μm. The secondary fiber has 5 cores and a core diameter of 12 μm.
[0068] (5) The secondary fibers were fixed on a glass sheet and placed in a tubular furnace for heat treatment at 330 °C for 10 min. The instability of the fluid in the fiber and the glass transition temperature difference between the cladding material and the core material were used to shrink the core material to form polymer microspheres.
[0069] (6) Place the heat-treated secondary fiber in a beaker containing 50 mL of N,N-dimethylacetamide, and heat it at 80°C and 600 rpm while stirring continuously to fully dissolve the polysulfone resin coating material. After the dissolution is complete, centrifuge the mixed solution at 12,000 rpm for 5 min to separate the polymer microspheres. In order to fully remove the coating material, re-add N,N-dimethylacetamide, sonicate for 10 min, and centrifuge again. Repeat this operation 7 times to fully remove the polysulfone resin coating. Finally, remove the upper layer of liquid and collect the precipitate to obtain the polymer microspheres.
[0070] In this embodiment, five core cavities are set in the second cladding rod, and the secondary fiber is stretched twice. The particle size of the polymer microspheres obtained by heat treatment of the secondary fiber is about 25 μm, and the number of the polymer microspheres obtained is about 2×10 4 Particles. Example 4
[0071] (1) The operation method for preparing the core material in this embodiment is basically the same as that in Example 1, except that the content of vinylene carbonate is 0.09 mL, the content of 2-ethylhexyloxytitanic acid is 15 μL, and the content of azobisisobutyronitrile is 9 mg. The specific process is not repeated here. In this embodiment, the mass ratio of vinylene carbonate to olefin-norbornene copolymer is 12.2:100, and the average molecular weight of the obtained vinylene carbonate modified olefin-norbornene copolymer is ≈235000, ∑(X i +Z i )≈965,∑Y i ≈282,∑W i ≈1273.
[0072] (2) The obtained mixed solution was made into a film with a thickness of 200 μm using a coating machine, and the vinylene carbonate-modified olefin-norbornene copolymer was placed in two semi-cylindrical molds with a diameter of 2 mm. The molds were hot-pressed at 230 °C for 15 min. After the internal air was fully expelled, a dense semi-cylinder was obtained. The two semi-cylinders were molded together and further hot-pressed to obtain a core layer rod with a diameter of 2 mm.
[0073] (3) Put the polysulfone resin masterbatch into a mold with a diameter of 30 mm, and hot press it at 300°C for 15 min. During this process, the pressure is continuously applied to ensure that the polysulfone resin masterbatch can be continuously subjected to pressure. Add material every 15 min until a dense cylindrical polysulfone resin rod is obtained, which is the first cladding rod with a diameter of 30 mm. Use a drilling machine to symmetrically drill a cylindrical core cavity with a diameter of 2 mm in the center of the first cladding rod, and the core cavity is set along the length direction of the cladding rod.
[0074] (4) Insert the core layer rod into the core cavity of the first cladding rod, place the first cladding rod in a vacuum drying oven, and heat cure it at 100°C for 30 min to obtain a primary preform rod, place the primary preform rod on a drawing tower, and perform the first stretching at 360°C to hot draw it into a primary fiber with a core-clad structure and a diameter of 600 μm. The core diameter is 40 μm.
[0075] (5) The primary fiber is fixed on a glass sheet and placed in a tubular furnace for heat treatment at 380°C for 8 min. The instability of the fluid in the fiber and the glass transition temperature difference between the cladding material and the core material are used to shrink the core layer to form polymer microspheres.
[0076] (6) Place the heat-treated secondary fiber in a beaker containing 50 mL of N,N-dimethylacetamide, and heat it at 90°C and 600 rpm while stirring continuously to fully dissolve the polysulfone resin coating material. After the dissolution is complete, centrifuge the mixed solution at 10,000 rpm for 5 min to separate the polymer microspheres. In order to fully remove the coating material, re-add N,N-dimethylacetamide, sonicate for 10 min, and centrifuge again. Repeat this operation 7 times to fully remove the polysulfone resin coating. Finally, remove the upper layer of liquid and collect the precipitate to obtain the polymer microspheres.
[0077] In this embodiment, the primary fiber is drawn once, and the particle size of the polymer microspheres obtained after the primary fiber is heat treated is about 90 μm, and the number of the polymer microspheres obtained is about 1.1×10 3 Particles. Example 5
[0078] Steps (1) and (2) in this embodiment are exactly the same as those in Embodiment 1 and will not be described again here.
[0079] (3) Put the polysulfone resin masterbatch into a cylindrical mold with a diameter of 20 mm and two cylindrical molds with a diameter of 30 mm, respectively, and hot press at 300°C for 15 min. During this process, the pressure is continuously applied to ensure that the polysulfone resin masterbatch can be continuously subjected to pressure. The material is added every 15 min until a dense polysulfone resin rod is obtained, of which the 20 mm diameter rod is the first cladding rod, and the other two 30 mm diameter rods are the second cladding rod and the third cladding rod. Use a drilling machine to symmetrically drill 5 cylindrical core cavities with a diameter of 2 mm in the center of the first cladding rod. The 5 core cavities are symmetrical about the axis of the first cladding rod, and 1 cylindrical core cavity with a diameter of 6 mm is drilled in the center of the second cladding rod and the third cladding rod respectively. The core cavity is set along the length direction of the cladding rod.
[0080] (4) Insert the core layer rod into the five core cavities of the first cladding rod, place the first cladding rod in a vacuum drying oven, and heat cure it at 100 °C for 30 min to obtain a primary preform rod. Place the primary preform rod on a drawing tower and perform the first stretching at 360 °C to heat draw it into a primary fiber with a diameter of 600 μm.
[0081] Take 70 primary fibers with consistent height and insert them into the core cavity of the second cladding rod. The second cladding rod is placed in a vacuum drying oven and heat-cured at 100°C for 30 min to obtain a secondary preform rod. The secondary preform is stretched for the second time at 360°C and hot-drawn into a secondary fiber with a diameter of 600 μm. The secondary fiber has 350 cores and a core diameter of 1.5 μm.
[0082] Take 70 secondary fibers with highly consistent diameters and insert them into the core cavity of the third cladding rod. The third cladding rod is placed in a vacuum drying oven and heat-cured at 100°C for 30 min to obtain a tertiary preform rod. The third stretching is carried out at 360°C to hot-draw it into a tertiary fiber with a diameter of 600 μm. The core number of the tertiary fiber is 24,500 and the core diameter is 0.024 μm.
[0083] (5) The tertiary fibers are fixed on a glass sheet and placed in a tubular furnace for heat treatment at 290 °C for 10 min to shrink the core material in the cladding material to form polymer microspheres.
[0084] (6) Place the heat-treated tertiary fiber in a beaker containing 40 mL of N,N-dimethylacetamide, and heat it at 50°C and 600 rpm while stirring continuously to fully dissolve the polysulfone resin coating material. After the dissolution is complete, centrifuge the mixed solution at 10,000 rpm for 5 min to separate the polymer microspheres. In order to fully remove the coating material, re-add N,N-dimethylacetamide, sonicate for 10 min, and centrifuge again. Repeat this operation 7 times to fully remove the polysulfone resin coating. Finally, remove the upper layer of liquid and collect the precipitate to obtain the polymer microspheres.
[0085] In this embodiment, five core cavities are set in the first cladding rod to obtain a primary fiber, and three stretchings are performed to obtain a tertiary fiber. The particle size of the polymer microspheres obtained after the heat treatment of the tertiary fiber is about 50 μm, and the number of the obtained polymer microspheres is about 1.4×10 7 Particles. Example 6
[0086] (1) The operation method for preparing the core material in this embodiment is basically the same as that in Example 1, except that the content of vinylene carbonate is 0.1 mL, the content of 2-ethylhexyloxytitanic acid is 20 μL, and the content of azobisisobutyronitrile is 10 mg. The specific process is not repeated here. In this embodiment, the mass ratio of vinylene carbonate to olefin-norbornene copolymer is 13.6:100, and the average molecular weight of the obtained vinylene carbonate modified olefin-norbornene copolymer is ≈250000, ∑(X i +Z i )≈1027,∑Y i ≈300,∑W i ≈1354.
[0087] (2) The obtained mixed solution was made into a film with a thickness of 200 μm using a coating machine, and the vinylene carbonate-modified olefin-norbornene copolymer was placed in two semi-cylindrical molds with a diameter of 25 mm. The molds were hot-pressed at 230 °C for 15 min. After the internal air was fully expelled, a dense semi-cylinder was obtained. The two semi-cylinders were molded together and further hot-pressed to obtain a core layer rod with a diameter of 25 mm.
[0088] (3) Put the polysulfone resin masterbatch into a mold with a diameter of 30 mm, and hot press it at 300°C for 15 min. During this process, the pressure is continuously applied to ensure that the polysulfone resin masterbatch can be continuously subjected to pressure. Add material every 15 min until a dense cylindrical polysulfone resin rod is obtained, which is the first cladding rod with a diameter of 30 mm. Use a drilling machine to symmetrically drill a cylindrical core cavity with a diameter of 25 mm in the center of the first cladding rod.
[0089] (4) Insert the core layer rod into the core cavity of the first cladding rod, place the first cladding rod in a vacuum drying oven, and heat cure it at 100°C for 30 min to obtain a primary preform rod, place the primary preform rod on a drawing tower, and perform the first stretching at 360°C to hot draw it into a primary fiber with a core-clad structure and a diameter of 600 μm. The core diameter is 500 μm.
[0090] (5) The primary fiber is fixed on a glass sheet and placed in a tube furnace for heat treatment at 380°C for 10 min to shrink the core material in the cladding material to form polymer microspheres.
[0091] (6) Place the heat-treated primary fiber in a beaker containing 50 mL of N,N-dimethylacetamide, and heat it at 60°C and 400 rpm while stirring continuously to fully dissolve the polysulfone resin coating material. After the dissolution is complete, centrifuge the mixed solution at 8000 rpm for 3 min to separate the polymer microspheres. In order to fully remove the coating material, re-add N,N-dimethylacetamide, sonicate for 10 min, and centrifuge again. Repeat this operation 7 times to fully remove the polysulfone resin coating. Finally, remove the upper layer of liquid and collect the precipitate to obtain the polymer microspheres.
[0092] In this embodiment, a primary fiber is obtained by a single stretching, and the particle size of the polymer microspheres obtained by heat treatment of the primary fiber is about 1500 μm, and the number of the polymer microspheres obtained is about 1.35×10 2 Particles.
[0093] Comparative Examples 1-4
[0094] In step (1) of Comparative Example 1-4, 1 g of olefin-norbornene copolymer was weighed and poured into 20 ml of toluene solution, and heated and stirred until completely dissolved. Comparative Example 1-4 is different from Example 1-4 in that the core layer material used in Comparative Example 1-4 is only olefin-norbornene copolymer, and the rest of the test process is exactly the same as that of Example 1-4.
[0095] According to the test, the particle size of the microspheres obtained in Comparative Examples 1 to 4 is not uniform. The particle size of the microspheres obtained in Comparative Example 1 is 2-3 μm, the particle size of the microspheres obtained in Comparative Example 2 is 8-10 μm, the particle size of the microspheres obtained in Comparative Example 3 is 25-30 μm, and the particle size of the microspheres obtained in Comparative Example 4 is 90-98 μm.
[0096] like Figure 8 As shown, it can be observed that the uniformity of the microspheres obtained in Comparative Example 1 is significantly reduced compared with that in Example 1, the microspheres in Comparative Example 1 have poor monodispersity, and the microspheres are obviously connected to each other. Fig. 9The surface changes of the microspheres obtained in Comparative Example 1 after being irradiated with high-energy electron beams for the same time as in Example 1 show that the surface of the microspheres obtained in Comparative Example 1 collapses and wrinkles significantly.
[0097] like Fig.10 and Fig.11 As shown, it can be clearly observed that the particle size distribution of the microspheres obtained in Comparative Example 2 is uneven and there are obvious connections between the microspheres. The smoothness of the microsphere surface is significantly worse than that of Example 2. Fig.10 It can be seen that some of the microspheres still have cladding materials that have not been fully removed. Fig.11 It can be seen that the spherical regularity of the microspheres is significantly worse than that of Example 2.
[0098] like Figure 7 , Fig.12 and Fig.13 As shown, the smoothness of the microsphere surface obtained in Comparative Example 4 is significantly worse than that in Example 4, and there are still many pores on the surface of the microsphere, such as Fig.13 As shown, there are not only pores on the surface of the microspheres, but also a polysulfone resin coating that has not been completely removed, and the microspheres are elliptical with poor sphericity.
[0099] It can be seen that compared with Comparative Examples 1-4, Examples 1-4 solve the problems of irregular pores, uneven particle size, poor monodispersity, and poor spherical regularity in the prepared microspheres caused by using only olefin-norbornene as the microsphere bulk material, thereby improving the application quality of the microspheres in various fields.
[0100] Table 1
[0101]
[0102] As shown in Table 1, it can be seen from Examples 1-6 that by increasing the number of core cavities in the cladding rods and the number of core layer rods or fibers placed in the core cavities, the number of cores of the final N-level fiber can be increased to increase the number of microspheres produced; and by increasing the number of fiber iterations, the number of microspheres produced can be increased exponentially, thereby achieving mass production of microspheres.
[0103] It can be seen from the results of Examples 1 and 5 and Examples 4 and 6 that the diameter of the microsphere can be adjusted by adjusting the diameter ratio between the first cladding rod and the core layer rod. The larger the diameter ratio, the smaller the microsphere diameter; and by increasing the number of fiber iterations, the particle size of the microsphere can be effectively controlled, thereby achieving controllable size of the microsphere from 50 nm to 2 mm.
[0104] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific embodiments described. Obviously, although the embodiments of the present invention have been shown and described, it is understood by those of ordinary skill in the art that many modifications and changes can be made without departing from the principles and spirit of the present invention. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing vinylene carbonate modified olefin-norbornene copolymer microspheres, characterized in that: The following steps are involved: (1) Preparation of core layer material: dissolving olefin-norbornene copolymer in toluene solution, stirring evenly at 40-50° C., adding vinylene carbonate and appropriate amounts of 2-ethylhexyloxytitanic acid and azobisisobutyronitrile, and obtaining a mixed solution containing vinylene carbonate modified olefin-norbornene copolymer after the reaction is completed, wherein the mass ratio of the added olefin-norbornene copolymer to the added vinylene carbonate is 100:(7-13.6); (2) Preparation of core layer rod: the mixed solution obtained in step (1) is formed into a film by a coating machine, and the film is subjected to heat pressing to obtain a cylindrical core layer rod; (3) Preparation of cladding rods: using cladding material masterbatch to be hot pressed at 290-310° C. to form N cylindrical cladding rods, where N is a natural number greater than 0, and at least one cylindrical core cavity is symmetrically arranged with the axis of the cladding rod as the symmetry axis, and the core cavity is arranged along the length direction of the cladding rod; (4) Preparation of N-grade fiber: A plurality of core layer rods are placed in each core cavity of the first cladding rod, vacuum heat treatment is performed to obtain a first-level preform rod, and the first-level preform rod is subjected to heat drawing treatment to obtain a first-level fiber. A plurality of primary fibers are placed in each core cavity of the second cladding rod, vacuum heat treatment is performed to obtain a secondary preform rod, and the secondary preform rod is heat-drawn to obtain a secondary fiber. ......... Inserting a plurality of N-1-level fibers into each core cavity of the N-th cladding rod, performing vacuum heat treatment to obtain an N-level preform rod, and performing heat drawing treatment on the N-level preform rod to obtain an N-level fiber; (5) Heat treatment of the N-grade fiber: heat treating the N-grade fiber obtained in step (4) for 3 to 10 minutes, so that the core layer material of the N-grade fiber shrinks in the cladding material to form microspheres; (6) Dissolving the cladding material: dissolving the N-grade fiber microspheres obtained in step (5) in a selective solvent for the cladding material, heating and stirring until completely dissolved, centrifuging at high speed for 5 minutes, then adding the selective solvent for the cladding material and ultrasonicating for 10 minutes, repeatedly centrifuging and ultrasonicating for multiple times, removing the upper liquid, collecting the precipitate to obtain vinylene carbonate modified olefin-norbornene copolymer microspheres, the structural formula of the vinylene carbonate modified olefin-norbornene copolymer is: , Where 0≤X i , 0≤Y i , 0≤Z i , 0≤W i , and X i , Y i , Z i Not at the same time 0, 821≤∑(X i +Z i )≤1027,240≤∑Y i ≤300,1083≤∑W i ≤1354.
2. The method for preparing vinylene carbonate modified olefin-norbornene copolymer microspheres according to claim 1, characterized in that: The temperature of the vacuum heat treatment in step (4) is 80-100°C and the time is 30 minutes; the temperature of the hot drawing treatment in step (4) is 280-360°C.
3. The method for preparing vinylene carbonate modified olefin-norbornene copolymer microspheres according to claim 1, characterized in that: The diameter of the core layer rod is 2-4 mm, the diameter of the cladding rod is 20-30 mm, the number of core cavities of each cladding rod is set to 1-5, and the diameter of the core cavity is 2-25 mm.
4. The method for preparing vinylene carbonate modified olefin-norbornene copolymer microspheres according to claim 3, characterized in that: The value range of N is 1 to 4.
5. The method for preparing vinylene carbonate modified olefin-norbornene copolymer microspheres according to claim 4, characterized in that: The diameter of the N-level fiber obtained in step (4) is 0.6 to 4 mm.
6. The method for preparing vinylene carbonate modified olefin-norbornene copolymer microspheres according to claim 1, characterized in that: The cladding material is polysulfone resin.
7. The method for preparing vinylene carbonate modified olefin-norbornene copolymer microspheres according to claim 6, characterized in that: The selective solvent of the cladding material is selected from one of N,N-dimethylacetamide solution, N-methylpyrrolidone solution and N,N-dimethylformamide solution.
Citation Information
Patent Citations
Ternary polymerization method of norbornenes, styrene and vinylene carbonate
CN108395502A